2012
DOI: 10.1007/s00425-012-1784-x
|View full text |Cite
|
Sign up to set email alerts
|

Immunolocalization of 8-5′ and 8-8′ linked structures of lignin in cell walls of Chamaecyparis obtusa using monoclonal antibodies

Abstract: Mouse monoclonal antibodies were generated against dehydrodiconiferyl alcohol- or pinoresinol-p-aminohippuric acid (pAHA)-bovine serum albumin (BSA) conjugate as probes that specifically react with 8-5' or 8-8' linked structure of lignin in plant cell walls. Hybridoma clones were selected that produced antibodies that positively reacted with dehydrodiconiferyl alcohol- or pinoresinol-pAHA-BSA and negatively reacted with pAHA-BSA and guaiacylglycerol-beta-guaiacyl ether-pAHA-BSA conjugates containing 8-O-4' lin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 24 publications
1
16
0
Order By: Relevance
“…The described safranin method is not only easy to use, but also provides high‐resolution spatial information on cell wall lignin that can usually only be obtained by using more time‐consuming and fastidious techniques, such as light/SEM immunolocalization or Raman spectroscopy (Gierlinger, ; Kiyoto et al , ; Day et al , ; Simon et al , ).…”
Section: Resultsmentioning
confidence: 99%
“…The described safranin method is not only easy to use, but also provides high‐resolution spatial information on cell wall lignin that can usually only be obtained by using more time‐consuming and fastidious techniques, such as light/SEM immunolocalization or Raman spectroscopy (Gierlinger, ; Kiyoto et al , ; Day et al , ; Simon et al , ).…”
Section: Resultsmentioning
confidence: 99%
“…The direct monitoring of cell wall lignification processes in live plants and cells is a promising strategy to gain insight into the elusive aspects of lignin biosynthesis. Unlike proteins, and similarly to polysaccharides or lipids, lignins are not amenable to being genetically tagged for (Lewis and Yamamoto, 1990;Donaldson, 2001;Fromm et al, 2003), direct microspectrophotometric detection (Singh et al, 2009;Sun et al, 2011;Ding et al, 2012;Gierlinger et al, 2012;Donaldson, 2013), mass spectrometry-based chemical imaging (Saito et al, 2005(Saito et al, , 2012Jung et al, 2012), and immunochemical labeling using lignin-specific antibodies (Ruel et al, 2009;Tranquet et al, 2009;Kiyoto et al, 2013), have been developed and used to visualize lignins in plant tissues. However, these methods typically involve several disadvantages either in sensitivity, specificity, sample-preparation times, artifacts from sample fixation, and/or applicability to living plant systems.…”
Section: Introductionmentioning
confidence: 99%
“…In contrast to outer-stem tissues, the S/G ratio (0.12) estimated from lbf12D NMR spectra (Supplemental Figure 1) was very similar to that estimated by thioacidolysis (0.13). Further information on lbf1 lignin was obtained using the KM1 antibody targeted against lignin phenylcoumaran linkages (b-5) (Kiyoto et al, 2013). TEM observation showed that labeling was present in the whole cell wall (primary cell wall, secondary cell wall) of lbf1 fibers, but was conspicuously absent in wild-type fibers (Figure 6).…”
Section: The Flax Lbf1 Mutant Has a Modified Lignin Contentmentioning
confidence: 99%